Analysis of Common Beta-Thalassemia (β-Thalassemia) Mutations in East Java, Indonesia - Hernaningsih, Yetti; Syafitri, Yuli; Indrasari, Yulia Nadar; Rahmawan, Prafa Alif; Andarsini, Mia Ratwita; Lesmana, Indra; Moses, Emmanuel Jairaj; Abdul Rahim, Nur Arzuar; Yusoff, Narazah Mohd (Frontiers in Pediatrics, 2022)
Background The frequency of the beta-thalassemia (β-thalassemia) gene in Indonesia ranges from 3 to 10%. However, in the East Java province, there is still limited information on the prevalence of β-thalassemia mutations in clinically diagnosed beta-thalassemia patients of East Java. Therefore, this study aimed to characterize β-thalassemia mutations in selected patients in the East Java province of Indonesia. Methods This is an analytical observational study. Diagnosis of β-thalassemia was based on clinical presentation, complete blood count (CBC), and hemoglobin (Hb) electrophoresis. Blood specimens taken from each patient in three ethylenediaminetetraacetic acid (EDTA) tubes were analyzed for CBC and Hb electrophoresis and processed for DNA extraction and subsequent polymerase chain reaction (PCR). Detection of mutations in Hemoglobin Subunit Beta (HBB) gene exons 1–3 of the β-thalassemia gene as the common mutation in Indonesia was done using PCR followed by Sanger sequencing. Results In total, 33 (n = 33) participants were involved in this study with ages ranging from 5 to 17 years comprising 19 women and 14 men. Their ethnic origins were Javanese (n = 30) and Chinese (n = 3). CBC results showed that mean ± standard deviation (SD) for Hb, red blood cell (RBC), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), and red cell distribution width (RDW)-CV were 81.2 ± 7.0 g/L; 3.40 ± 0.39 × 109/L; 71.05 ± 5.72 fL; 24.12 ± 2.45 pg; 33.91 ± 1.47 g/dl; 24.38 ± 6.02%, respectively. Hb electrophoresis revealed that 5 out of 33 participants had beta-thalassemia and 28 out of 33 participants had hemoglobinopathy (Hb) E/beta-thalassemia. Results of Sanger sequencing showed the following genotype variations in the samples: 12 (36.4%) with βCD26/βIVS−I−5; 6 (18.2%) with βCD26/βCD35; 3 (9.1%) with βCD26/βIVS−I−2; 2 (6.1%) with βCD27/28/βCD40; 2 (6.1%) with βIVS−I−1/βCAP+1; and βCD26/βIVS−I−1; βIVS−I−5/βCAP+1; βIVS−I−5/βCD35; βCD26/βCD37; βCD26/βCD15; βCD26/βCD40; and βIVS−I−5/βCD19 in 1 (3%) sample, respectively, and 1 (3%) had no abnormality detected in sequencing even though electrophoresis showed abnormality in the migration pattern. The βCD26/βIVS−I−5 mutation was found in samples that were noted to have Hb E/beta-thalassemia on Hb electrophoresis. Conclusion The underlying genetic variations are heterogeneous in thalassemia patients in East Java, where 12 variants were found. The most common variant was βCD26/βIVS−I−5, which all accounted for Hb E/beta-thalassemia on Hb electrophoresis. Furthermore, 28 out of 33 participants had hemoglobinopathy (Hb) E/beta-thalassemia.